Follow the Leader? Price Change Timing in Internet-Based Selling - Kauffman, R. J. (Institutional Knowledge at Singapore Management University, 2007)
Internet technologies should lessen information asymmetry, prompting competitive price reactions, but this does not seem to be happening in Internet-based selling. We study empirical regularities of price change timing for music CD vendors and booksellers to assess several theoretical explanations. Our sample includes 123, 680 daily prices for 169 products and 53 firms. Bertrand competition is insufficient to explain our observation that sellers do not shift prices this way. Tacitly collusive responses to competitors' price changes are observed rather than price changes solely in response to demand or cost shifts as would be expected with Bertrand competition. We find evidence of business rules for strategic pricing associated with tacitly collusive pricing and Edgeworth competition. Copyright © 2007 John Wiley & Sons, Ltd.